Coffin-Siris Syndrome 4-Related Spectrum in a Young Woman Caused by a Heterozygous SMARCA4 Deletion Detected by High-Resolution aCGH - Mitrakos, Anastasios (Mol Syndromol, 2020)
Coffin-Siris Syndrome 4 is an autosomal dominant congenital malformation syndrome caused by heterozygous mutations in the SMARCA4 gene with its main features being intellectual disability, developmental delay, behavioral abnormalities, and hypoplastic or absent fifth fingernails and fifth distal phalanges. Here, we report a young woman with developmental delay, moderate intellectual disability, and bilateral sensorineural hearing loss, referred for genetic testing. High-resolution chromosomal microarray analysis identified a 428-kb deletion in chromosome 19 which included the SMARCA4 gene. We conclude that haploinsufficiency of SMARCA4 may be a valid pathophysiological mechanism leading to milder Coffin-Siris syndrome phenotypes.